Re-emergence of T lymphocyte-mediated synaptopathy in progressive multiple sclerosis - Sanna, Krizia; Bruno, Antonio; Balletta, Sara; Caioli, Silvia; Nencini, Monica; Fresegna, Diego; Guadalupi, Livia; Dolcetti, Ettore; Azzolini, Federica; Buttari, Fabio; Fantozzi, Roberta; Borrelli, Angela; et al. (Frontiers in Immunology, 2024)
Background: Secondary progressive multiple sclerosis (SPMS) is defined by the irreversible accumulation of disability following a relapsing-remitting MS (RRMS) course. Despite treatments advances, a reliable tool able to capture the transition from RRMS to SPMS is lacking. A T cell chimeric MS model demonstrated that T cells derived from relapsing patients exacerbate excitatory transmission of central neurons, a synaptotoxic event absent during remitting stages. We hypothesized the re-emergence of T cell synaptotoxicity during SPMS and investigated the synaptoprotective effects of siponimod, a sphingosine 1-phosphate receptor (S1PR) modulator, known to reduce grey matter damage in SPMS patients. Methods: Data from healthy controls (HC), SPMS patients, and siponimod-treated SPMS patients were collected. Chimeric experiments were performed incubating human T cells on murine corticostriatal slices, and recording spontaneous glutamatergic activity from striatal neurons. Homologous chimeric experiments were executed incubating EAE mice T cells with siponimod and specific S1PR agonists or antagonists to identify the receptor involved in siponimod-mediated synaptic recovery. Results: SPMS patient-derived T cells significantly increased the striatal excitatory synaptic transmission (n=40 synapses) compared to HC T cells (n=55 synapses), mimicking the glutamatergic alterations observed in active RRMS-T cells. Siponimod treatment rescued SPMS T cells synaptotoxicity (n=51 synapses).Homologous chimeric experiments highlighted S1P5R involvement in the siponimod's protective effects.Transition from RRMS to SPMS involves the reappearance of T cell-mediated synaptotoxicity. Siponimod counteracts T cell-induced excitotoxicity, emphasizing the significance of inflammatory synaptopathy in progressive MS and its potential as a promising pharmacological target.